Diet Quality and Growth Status of Children Aged Two to Six Years at Tuba Island, Langkawi, Malaysia - Salleh, Nor Wasiqaho; Hamid, Syahrul Bariah; Md Nor, Norazmir; Shuhaimi , Farhanah Ahmad; Kamarul Zaman, Mazuin; Ismail, Nazrul Hadi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
This study aimed to determine the prevalence of undernutrition, diet quality and its associated factors among children aged two to six years at Tuba Island. A total of 67 children paired with their mother or caregiver were participated in this study. A questionnaire containing socio-demographic characteristics, anthropometric measurements and two days of 24-hours dietary recall was administered. The Malaysian Healthy Eating Index (HEI) was used to assess the children’s diet quality. The prevalence of underweight, stunting and wasting were 22.4%, 20.8% and 17.9%, respectively. Mean total HEI score was 37.1±6.3, which indicate poor diet. The children had low mean scores for vegetables, fruits, milk and dairy products as well as legumes. For socio-demographic factors, number of children per household was associated with diet quality. This study points out that overall low dietary score among these children and their diet quality had no association with their growth status. The low diet quality was prevalent; thus it did not contribute to differences in growth status among these children. Therefore, it is suggested further intervention should be taken to improve the nutrition quality of these children.